The Ethnoscience-Based Project Based Learning Model on Learning Outcomes and Scientific Literacy - Rifa’i, Mohamad; Taufik, Leo Muhammad; Novianawati, Noor (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Many students struggle to understand science because it's too abstract and removed from life. Despite their scientific value, local wisdom and traditional knowledge are typically neglected as learning resources. The connection between universal science and local cultures is referred to as ethnoscience. In ethnoscience-based PjBL, students learn theory and observe how science applies to their culture. Therefore, this study intends to determine and describe the effect of the ethnoscience-based project-based learning (PjBL) learning model on learning outcomes and scientific literacy. This study uses quantitative research with ex post facto research method. The subjects of this study were class VII students of Middle School 4 Palimanan, Cirebon Regency. Data collection uses questionnaires, observations, and test questions with a total of 30 items, and the number of samples (respondents) used is 60 students. The results of this study indicate that the application of the ethnoscience-based project-based learning model positively affects the learning outcomes of class VII students in science subjects, as evidenced by a calculated t value of 4.637 compared to a t table value of 1.672, resulting in an influence of 25.8%, while the remaining 74.2% is affected by other unexamined variables. Similarly, the application of the ethnoscience-based Project Based Learning model enhances the scientific literacy of seventh-grade science students. The influence is shown based on the calculated t value of 7.537 > t table = 1.672, with a 48.6% effect, while the remaining 51.4% is influenced by other variables not examined in this study. This research will produce a structured ethnoscience-based PjBL learning model that can be used as a guide for teachers.